Application of LC–MS in the Development of Natural Product–Based Antidepressant Drugs: A Systematic Literature Review - Ridel Yosua Rumondor; Novi Yantih; Kholilah; Nur Pujiastuti (Journal of Natural Product for Degenerative Diseases, 2026)
Due to the shortcomings of existing medications, depression remains a worldwide neuropsychiatric disorder requiring innovative therapeutic strategies. Natural compounds represent promising multi-target antidepressant candidates; however, their chemical complexity necessitates advanced analytical tools. This systematic literature review assessed the application of liquid chromatography–mass spectrometry (LC–MS) in the identification, profiling, and standardization of natural antidepressant compounds. A comprehensive search of major databases was conducted following PRISMA guidelines for studies published between 2014 and 2024, with a total of six eligible studies were included in the qualitative synthesis.. The findings indicate that LC–MS, particularly high-resolution platforms such as QTOF and Orbitrap, is the primary method for metabolite profiling and dereplication of bioactive classes including flavonoids, alkaloids, and phenolic acids. Integration of LC–MS data with in vitro and in vivo models has facilitated the correlation of chemical profiles with pharmacological mechanisms, such as neurotransmitter regulation. Despite its pivotal role in evidence-based natural product research, challenges remain in analytical standardization and clinical translation. In conclusion, LC–MS is an indispensable and transformative tool in the development of natural product-based antidepressants, providing robust chemical characterization that supports pharmacological validation and accelerates drug discovery. Future research should emphasize methodological harmonization and systems biology integration to enhance translational impact.